MINANGKABAU MATRILINEAL RELATIONSHIP IN THE LOVE FOR SALE 2 FILM - Maharani, Anita Devi; Hudoyo, Sapto (Capture : Jurnal Seni Media Rekam, 2022)
Love for Sale 2 chronicles the life of a Minangkabau family living overseas. This tribe is highly distinctive due to the embraced and lived matrilineal culture. Accordingly, this study seeks to denote and connote the Minangkabau matrilineal relationship in the Sikumbang family as depicted in the film Love for Sale 2 by combining the descriptive method with Roland Barthes' semiotics in the analysis. The purposive sampling method selects scene samples. The findings of this study indicate that the Sikumbang family maintains the Minangkabau matrilineal relationship, which includes marriage as a communal affair, the importance of obtaining an ideal son-in-law, the'mamak-kemenakan' relationship, the 'bako anak pisang' relationship, and the mother's role in a matrilineal family.